EVALUATION OF THE EFFECTIVENESS OF PERSONAL HEAD PROTECTION EQUIPMENT IN ARMY AVIATION AND WAYS TO IMPROVE THEM - V.V. Kharitonov; P.M. Sheshegov; V.N. Zinkin (Измерение, мониторинг, управление, контроль, 2022)
Background. The purpose of the work was to evaluate the effectiveness of personal protective equipment of the head used in army aviation, identify shortcomings and justify ways to improve them. Materials and methods. We investigated the means of protecting the heads of flight crews, which are currently used in state aviation. The work used a subjective method (questionnaire) and an objective method for evaluating acoustic efficiency. Special attention was paid to the protective equipment used in army aviation, since helicopter noise has a number of features. The sources and mechanisms of helicopter noise formation are shown. Results. With the help of a questionnaire, sound-proofing, constructive, operational and ergonomic disadvantages of personal head protection equipment were identified. A comparison of the soundproofing properties of head protection products with acoustic parameters in the workplace showed their insufficient effectiveness, which creates risks of hearing loss. Conclusions. Recommendations are given to improve the transmission and perception of sound information of head protection devices used in state aviation, as well as evaluating the acoustic effectiveness of aircraft noise protection equipment.